ENHANCING CHEMISTRY LEARNING THROUGH A CRITICAL THINKING ASSESSMENT TOOL - Tiwi Nur Astuti; Sarina Hanifah; Retno Ayu Puspita; Gusman Santika (Jurnal Santiaji Pendidikan (JSP), 2026)
This study aims to develop a critical thinking skills instrument in chemistry learning, especially in chemical bonding material. This instrument was developed in 4 steps, namely determining aspects, compiling indicators, compiling questions, and validation which includes content validation and empirical validation. Content validation was carried out by 2 expert lecturers. The critical thinking skills question instrument was analyzed using Aiken V. The results of the analysis showed that out of 6 questions, all had a validity coefficient value of more than 0.35 and were declared valid. The empirical validation stage involved 275 students. The empirical validation analysis was carried out using the Rasch model. Based on the results of the analysis, 6 fit questions were obtained and had a cronbach's alpha reliability estimate value of 0.82 and were reliable for use in measuring students' critical thinking skills.